OVERVIEW OF STRESS COPING STRATEGIES FOR ELDERLY CAREGIVERS IN SOCIAL SERVICE CENTERS - Exlesia Wening Sukma; Erik Adik Putra Bambang Kurniawan; Nurlia Ikaningtyas; Antonius Yogi Pratama (Sahabat Publikasi Kuu, 2024)
Background: Coping strategies are changes in thinking and behavior that occur in a person in facing pressure from the environment in the form of stressors. Yogyakarta Special Region is the province with the highest percentage of elderly at 15.52%. Many families choose to entrust the elderly to live in an orphanage. The high level of daily activity carried out by the elderly can increase the physical burden of their caregivers. In this regard, the stressors that arise as a result of caring for the elderly require caregivers to have different coping strategies from each other.Purpose: This research aims to determine the description of stress coping strategies among elderly caregivers at service centersMethods: This research design uses non-experimental descriptive quantitative research methods. The sampling technique used total sampling with a total sample of 34 caregivers. The measuring tool uses The Ways of Coping questionnaireResults: The results show that the majority of caregivers, 55.9%, use Problem Focused Coping (PFC). In coping strategies based on respondent characteristics, the results showed that gender, age, marital status and length of work all used PFC. Then, based on education level, the results showed that high school graduates used Emotional Focused Coping (EFC) and D3/Bachelor graduates used PFC. Furthermore, in terms of characteristics based on religion, the results showed that Muslim caregivers used PFC and Catholic caregivers used both.Conclusions: The majority of categories of stress coping strategies used by elderly caregivers are Problem Focused Coping Keywords: stress coping strategies, elderly caregivers